Cover Picture: Macromol. Mater. Eng. 8/2014. Issue 8 (August 2014) - Fernandez, Javier G.; Ingber, Donald E.
<x xml:space="preserve">Abstract</x> Cover: A chess piece made of a chitosan‐based composite (queen) behind a commercial chess piece (king). The study on the correlation between molecular arrangement and mechanical characteristics of chitinous materials leads to use of the second most abundant biopolymer on earth for manufacture of several large‐scale 3D objects and composites. Further details can be found in the article by J. G. Fernandez and D. E. Ingber* on page 932. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>